Chitosan-Gelatin-Pectin Composite Films from Polyion-Complex Hydrogels - Zheng, X.F.; Lian, Q.; Song, S.T. (Asian Journal of Chemistry, 2013)
Preparation and properties of composite films from gelatin, chitosan and pectin hydrogels are presented. Ionic interactions between positively charged gelatin and negatively charged pectin produce reversible physical hydrogels with homogeneous molecular arrangement that improve water resistance but not alter thermal stability relative to single polymer gels. The effect of preparation conditions to the swelling rate and drug delivery of chitosan-gelatin-pectin films were also studied. Resulting interspersed permanent chemical hydrogel showed a decreased swelling attitude with the increased dosage of crosslinker. However, further the films improved higher permeation in simulated colonic fluid compared to the other media. The amount of bovine serum albumin released from the films at different time intervals was estimated by UV spectrophotomertic method at 279 nm. The dissolution profile and in vitro release kinetics showed that chitosan-gelatin-pectin films were promising for controlled delivery of the drug. Formulation containing pectin, chitosan and gelatin may be suitable as a coating formulation for colon targeted drug delivery.